Modelagem matemática com funções trigonométricas - PINHEIRO, Danilo Pablo Pinheiro (2024)
Observing nature is a human behavior, perceived since ancient times, necessary to provide knowledge and evolution of humanity. Over the years, techniques and means of specific description of nature were acquired, with the aim of providing man with improvements in daily activities and well-being. Natural phenomena, such as rain, are necessary to maintain life on earth, however, depending on their intensity, they can cause damage, both to humanity and nature. The capital of Pará, Belém, has the highest rainfall rates in the state of Pará, having an annual cycle of rainy and less rainy periods, which sometimes cause inconvenience for the population, causing flooding and damage to health. When dealing with means for describing preferences, mathematical modeling is a research method that uses mathematical concepts to produce tools that help in describing or making decisions about them. Linked to the description of cyclical characteristics and mathematics, trigonometric functions are mathematics study tools that behave by forming repetitions, commonly used to describe cyclical characteristics. Therefore, in this work, a trigonometric function will be used as a model to describe the behavior of precipitation in Belém, using data from ten years, Mathematical modeling and R’studio software.